Influence Massage Effleurage use Olive Oil (Olive Oil) to Flow of Mother's Milk Water Mom Post Partum - Fatrin, Tiara; Aryanti, Aryanti; Sari, Yona; Epriyani, Merita (GLOBAL HEALTH SCIENCE GROUP, 2024)
Breast milk is the ideal food in meeting the nutritional needs of newborns. Breast milk provides the energy and nutrients needed for the development and growth of the baby. In Indonesia, only 48.2% of mothers provide exclusive breastfeeding because their breast milk is not smooth. Breast milk can prevent LBW, premature birth, and can reduce infant mortality. One of the efforts to facilitate breastfeeding is with effleurage massage using olive oil. This effleurage massage can stimulate the release of oxytocin hormone. The purpose of this study was to determine the effect of effleurage massage using olive oil (Olive Oil) on the smoothness of breast milk in post partum mothers at PMB Lismarini Palembang. This type of research uses quasi-experimental with a one group pretest-posttest research design. Sampling was done by accidental sampling technique on 15 post partum mothers. Data were analyzed using the chi-square test. The data collection process is that the researcher explains the purpose of the study, if willing to become a respondent, then the researcher asked for willingsess to sign the consent sheet. if prospective respondents are not willing, the research must not impose and must respect the rights of prospective respondent. After the respondent is willing to become a respondent, the research gives a breast milk fluency questionnaire on day 1. After being given the questionnaire, it can be taken as a respondent according to with the inclusion criteria and the results were recorded on the sheet, then the provision of the effleurage massage started on days 1-4. Giving effleurage massage is done 3x/day, namely morning, afternoon, and evening night. On the first day in the morning the researcher gave the effleurage massage and continued by the husband effleurage and continued by the husband had been taught the researcher message techniques on the first day. Giving effleurage massage is done for 4 days with 3-5 minutes. On the 4th day after giving effleurage massage, the researcher gave the questionnaire again, during the research period April-May 2024. The sample obtained was 15 mothers. a little later.The results showed the effect of effleurage massage using olive oil on the smoothness of breast milk, obtained a p value of 0.039.